UTE MRI technical developments and applications in osteoporosis: a review - Shin, Soo Hyun; Chae, Hee Dong; Suprana, Arya; Jerban, Saeed; Chang, Eric Y.; Shi, Lingyan; Sah, Robert L.; Pettus, Jeremy H.; Woods, Gina N.; Du, Jiang (Frontiers in Endocrinology, 2025)
Osteoporosis (OP) is a metabolic bone disease that affects more than 10 million people in the USA and leads to over two million fractures every year. The disease results in serious long-term disability and death in a large number of patients. Bone mineral density (BMD) measurement is the current standard in assessing fracture risk; however, the majority of fractures cannot be explained by BMD alone. Bone is a composite material of mineral, organic matrix, and water. While bone mineral provides stiffness and strength, collagen provides ductility and the ability to absorb energy before fracturing, and water provides viscoelasticity and poroelasticity. These bone components are arranged in a complex hierarchical structure. Both material composition and physical structure contribute to the unique strength of bone. The contribution of mineral to bone’s mechanical properties has dominated scientific thinking for decades, partly because collagen and water are inaccessible using X-ray based techniques. Accurate evaluation of bone requires information about its components (mineral, collagen, water) and structure (cortical porosity, trabecular microstructure), which are all important in maintaining the mechanical integrity of bone. Magnetic resonance imaging (MRI) is routinely used to diagnose soft tissue diseases, but bone is “invisible” with clinical MRI due to its short transverse relaxation time. This review article discusses using ultrashort echo time (UTE) sequences to evaluate bone composition and structure. Both morphological and quantitative UTE MRI techniques are introduced. Their applications in osteoporosis are also briefly discussed. These UTE-MRI advancements hold great potential for improving the diagnosis and management of osteoporosis and other metabolic bone diseases by providing a more comprehensive assessment of bone quantity and quality.